THE IMPORTANCE OF COMPETENCE AND CAREER DEVELOPMENT TOWARDS EMPLOYEE PERFORMANCE IN MEDIATION OF MOTIVATION VARIABLES IN BI MONEY MANAGEMENT WORK UNITS (SATKER) IN JAVA ISLAND - Damara Sakti, Deri; Deden Kurniawan (Dinasti International Journal of Digital Business Management, 2022)
Basically, this study aims to examine and analyze the importance of competence and career development on employee performance by using the motivation variable as a mediating variable in the BI Money Management work unit in Java. By using a quantitative research design with an explanatory survey method , namely data collection using a questionnaire with a Likert scale model. The sample collection of organic employee respondent data is 300 respondents. Structural Equation Modeling (SEM) PLS Version 3.2.9 is used as a tool to process data. In this study using four variables, fourteen dimensions and thirty-six indicators. From the results of this study it can be concluded that all variables have a significant effect on employee performance, namely: 1) Competence on employee performance. 2) Career development on employee performance, 3) Motivation on employee performance, 4) Competence on motivation, 5) Career development on motivation, 6) Motivation mediates the effect of competence on employee performance, 7) Motivation mediates the effect of career development on employee performance.